A new genus of tiger beetle (Coleoptera: Cicindelidae) from the Nearctic and Neotropical realms - Duran, Daniel P.; Gough, Harlan M. (Zootaxa, 2022)
The taxonomically problematic tiger beetle species, Cylindera lemniscata (LeConte, 1854), has been difficult to place within the Nearctic fauna because of its peculiar morphological characteristics which were noted in its description, and by subsequent workers. Molecular phylogenetic studies of the late 1990s and early 2000s were similarly unable to reach a consensus about its systematic placement. More recently, a densely sampled mtDNA genealogy recovered Cy. lemniscata as a monotypic clade that is sister to a larger clade of Nearctic tiger beetles that included species of Dromochorus Guérin-Méneville, 1845, Ellipsoptera Dokhtouroff, 1883 and Parvindela Duran & Gough, 2019. In this present study, morphological characters were assessed for Cy. lemniscata and all of the above taxa, as well as members of the genus Brasiella Rivalier, 1954 and Cicindelidia cardini (Leng & Mutchler, 1916), a poorly known Cuban endemic with markings that are remarkably similar to Cy. lemniscata. The consensus of molecular and morphological analyses indicates that Cy. lemniscata is not congeneric with any other species, and as such, we erect Jundlandia Duran & Gough 2022, new genus, to accommodate this unique taxon. Future molecular work may determine that Ci. cardini may belong in Jundlandia.